2011
DOI: 10.2478/v10099-011-0004-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring and Promoting Ecological Consciousness in Teacher Education: the Possibilities of Educational Action Research in Education for Sustainable Development

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
0
10
0
5
Order By: Relevance
“…Through the process of engaging in action research, teachers gain deep insights into how they are working whilst looking forward to their future practices (Kraft, 2002) which enables them to ëtransformí in their thoughts, feelings and actions in a paradigm shift. Gedzune and Gedzune (2011) concluded that students through action research developed reflective skills on ecological consciousness and building sustainable and inclusive relationships with the world. In a study by Salite (2008), teachersí research skills were developed by involving them in action research.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Through the process of engaging in action research, teachers gain deep insights into how they are working whilst looking forward to their future practices (Kraft, 2002) which enables them to ëtransformí in their thoughts, feelings and actions in a paradigm shift. Gedzune and Gedzune (2011) concluded that students through action research developed reflective skills on ecological consciousness and building sustainable and inclusive relationships with the world. In a study by Salite (2008), teachersí research skills were developed by involving them in action research.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…These were all theoretical papers or papers containing case studies or qualitative methodology. The divide between anthropocentric/non-anthropocentric approaches was used in articles by SalÓte, Ged˛˚ne and Ged˛˚ne (2009), Kostoulas-Makrakis (2010), Ged˛˚ne and Ged˛˚ne (2011), and Buttigieg and Pace (2013) ñ these authors used this divide mainly to evaluate the views of research participants. The critique of anthropocentrism was oriented mostly toward normative definitions and approaches in the field of sustainability (Bentham, 2013;Cutanda & Murga-Menoyo, 2014;Eriksen, 2013;Mandolini, 2007;Pipere & MiËule, 2014;Smith, 2011).…”
Section: Research Paradigms (Jtefs 2005ñ2014)mentioning
confidence: 99%
“…Thus, by means of this project, a transversal and interdisciplinary treatment of environmental education will be promoted in different teacher training programmes. In that way, due to the great influence of teachers and teaching as agents of change in society, this educational experience developed in teacher training programmes is expected to contribute to the attainment of the environmental education objectives and to promote the sustainable development (Fien, 1995;Ilisko, 2007;Ged˛˚ne & Ged˛˚ne, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…/jtes-2014 people, society and the environment (Hicks & Holden, 1995;United Nations [UN], 1992). Consequently, it is necessary to incorporate respect for nature in educational programmes so that society becomes aware of the environmental problems and interacts with nature in a sustainable way (Ged˛˚ne & Ged˛˚ne, 2011;Wellie, 2002).…”
Section: Introductionmentioning
confidence: 99%